2022
DOI: 10.1097/qai.0000000000002825
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status and Cognitive Function in Children With HIV: Evidence From the HIV-Associated Neurocognitive Disorders in Zambia (HANDZ) Study

Abstract: Background: Multiple previous studies have identified a detrimental effect of pediatric HIV on cognitive function. Socioeconomic status (SES) is one of the strongest predictors of cognitive performance and may affect the relationship between HIV and cognition.Methods: As part of the ongoing HIV-Associated Neurocognitive Disorders in Zambia (HANDZ) study, a prospective cohort study, we recruited 208 participants with HIV and 208 HIV-exposed uninfected controls, all aged 8-17 years. A standardized questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…The current analysis focuses on a relatively limited cognitive battery that was performed every 3 months; future analyses will report the more comprehensive battery that was performed at annual intervals. However, our analysis of the comprehensive battery at baseline 36 suggested a similar result.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The current analysis focuses on a relatively limited cognitive battery that was performed every 3 months; future analyses will report the more comprehensive battery that was performed at annual intervals. However, our analysis of the comprehensive battery at baseline 36 suggested a similar result.…”
Section: Discussionsupporting
confidence: 69%
“…Demographic and health data were collected at baseline using structured interviews with participants and their parents and chart review. Measures of socioeconomic status were combined into a socioeconomic status index (SESI; see Mbewe et al 36 2022 for details). Nutritional status was assessed using a combination of structured interviews, record review, and growth curves.…”
Section: Methodsmentioning
confidence: 99%
“…Children in the rural areas were accessing care at the ART clinic associated with their residential catchment area. In contrast, the urban cohort were children seeking care at Zambia's largest tertiary care children's hospital and previous work has shown that children accessing care at this site are among the most economically deprived in the city 33,34 . Seizure severity burden was high with children presenting many hours after the index seizure onset with fulminant status epilepticus and/or coma.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, the urban cohort were children seeking care at Zambia's largest tertiary care children's hospital and previous work has shown that children accessing care at this site are among the most economically deprived in the city. 33,34 Seizure severity burden was high with children presenting many hours after the index seizure onset with fulminant status epilepticus and/or coma. Acute seizure management options are quite constrained in Zambia relative to high-income settings and intubation for ventilation is not de facto available even at the Teaching Hospitals for such cases.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that performance in cognitive tasks may be tempered by factors and influences not related to HIV disease and highlights the importance of having an appropriate comparison group [ 4 , 19 , 22 ]. However, a longitudinal analysis comparing cognitive testing performance in children with perinatally acquired HIV and HIV-exposed but uninfected children in Zambia, recently reported that socioeconomic factors impacted testing performance in both groups, but with a more marked effect in the PHIV group [ 23 ]. Another study in South Africa showed uninfected children exposed to maternal HIV infection had language delays at 2 years of age, so further work is needed to understand developmental outcomes of this population [ 24 ].…”
Section: Discussionmentioning
confidence: 99%